2005
DOI: 10.1007/s00021-004-0140-8
|View full text |Cite
|
Sign up to set email alerts
|

Scherk-Type Capillary Graphs

Abstract: Abstract. This paper concerns the regularity of a capillary graph (the meniscus profile of liquid in a cylindrical tube) over a corner domain of angle α. By giving an explicit construction of minimal surface solutions previously shown to exist (Indiana Univ. Math. J. 50 (2001), no. 1, 411-441) we clarify two outstanding questions.Solutions are constructed in the case α = π/2 for contact angle data (γ 1 , γ 2 ) = (γ, π − γ) with 0 < γ < π. The solutions given with |γ − π/2| < π/4 are the first known solutions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…We will construct an appropriate "capillary graph" (for example, [Huff and McCuan 2006]) using a Weierstrass representation of minimal surfaces. We assume the domain is symmetric about the coordinate axes and starshaped as indicated in Figure 1.…”
Section: Construction Of the Domains And Main Theoremsmentioning
confidence: 99%
See 3 more Smart Citations
“…We will construct an appropriate "capillary graph" (for example, [Huff and McCuan 2006]) using a Weierstrass representation of minimal surfaces. We assume the domain is symmetric about the coordinate axes and starshaped as indicated in Figure 1.…”
Section: Construction Of the Domains And Main Theoremsmentioning
confidence: 99%
“…The study of capillary surfaces in wedge domains can be tricky, as illustrated by [Keller et al 1991] and [Vreeburg 1990]. Concus and Finn [1991] mentioned that [Vreeburg 1990] was incorrect; we note that its argument is invalid since it does not distinguish between mean curvature and Gauss curvature and since it ignores [Tam 1986].…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Lieberman [1988] and Miersemann [1989] showed that such solutions are Hölder differentiable at O. Huff and McCuan [2006] gave examples to show that solutions need not be twice differentiable at O.…”
Section: Introductionmentioning
confidence: 99%